Macropinocytosis: a pathway to protozoan infection - de Carvalho, Tecia M. U.; Barrias, Emile S.; de Souza, Wanderley (Frontiers in Physiology, 2015)
Among the various endocytic mechanisms in mammalian cells, macropinocytosis involves internalization of large amounts of plasma membrane together with extracellular medium, leading to macropinosome formation. These structures are formed when plasma membrane ruffles are assembled after actin filament rearrangement. In dendritic cells, macropinocytosis has been reported to play a role in antigen presentation. Several intracellular pathogens are internalized by host cells via multiple endocytic pathways and macropinocytosis has been described as an important entry site for various organisms. Some bacteria, such as Legionella pneumophila, as well as various viruses, use this pathway to penetrate and subvert host cells. Some protozoa, which are larger than bacteria and virus, can also use this pathway to invade host cells. As macropinocytosis is characterized by the formation of large uncoated vacuoles and is triggered by various signaling pathways, which is similar to what occurs during the formation of the majority of parasitophorous vacuoles, it is believed that this phenomenon may be more widely used by parasites than is currently appreciated. Here we review protozoa host cell invasion via macropinocytosis.